2020
DOI: 10.21203/rs.3.rs-135608/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oleandrin Induces Immunogenic Cell Death Via the PERK/elF2α/ATF4/CHOP Pathway in Breast Cancer

Abstract: Background Chemotherapeutic agents have been linked to immunogenic cell death (ICD) induction that is capable of augmenting antitumor immune surveillance. The cardiac glycoside oleandrin, which inhibits Na+/K+-ATPase pump (NKP), has been shown to suppress breast cancer growth via inducing apoptosis. However, the implications of oleandrin in antitumor immune response and potential ICD induction remain unexplored till now, which is investigated in the present study.Methods Calreticulin (CRT) exposure was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…It was shown by Li et. al [113] that after administration of oleandrin to BALB/c mice with engrafted murine breast cancer cell line EMT6 and tumor-bearing mice intraperitoneally (0.3 mg/kg and 0.6 mg/kg) every day tumor growth was suppressed and the amount of tumor-infiltrating lymphocytes including dendritic cells and CD8+ T-cells were increased. In another study it was shown that ouabain (0.56 mg/kg with 140 mg/kg sodium succinate of hydrocortisone ) injected intraperitonially induced the death of immature double positive lymphocytes (CD4+CD8+) whereas CD69+ cells survived after both treatments [114].…”
Section: T-cells Cd8+ (Cytotoxic T Lymphocytes)mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown by Li et. al [113] that after administration of oleandrin to BALB/c mice with engrafted murine breast cancer cell line EMT6 and tumor-bearing mice intraperitoneally (0.3 mg/kg and 0.6 mg/kg) every day tumor growth was suppressed and the amount of tumor-infiltrating lymphocytes including dendritic cells and CD8+ T-cells were increased. In another study it was shown that ouabain (0.56 mg/kg with 140 mg/kg sodium succinate of hydrocortisone ) injected intraperitonially induced the death of immature double positive lymphocytes (CD4+CD8+) whereas CD69+ cells survived after both treatments [114].…”
Section: T-cells Cd8+ (Cytotoxic T Lymphocytes)mentioning
confidence: 99%
“…Cellular and systemic effects of cardiotonic steroids on different blood cells. Inhibition of the growth of melanoma tumors in murine model[115] (2) Reversed the inability of Cisplatin to trigger calreticulin exposure, and HPMA copolymer-amplified Cisplatininduced ATP release in melanoma mice model[116] Oleandrin(1) Inhibite tumor growth and increase tumor-infiltrating lymphocytes including dendritic cells and T cells[113] B cells OBN (1) Decrease the level of B-cells in bone marrow, spleen and peripheral blood in 24 hours Immunobiology [117]. …”
mentioning
confidence: 99%